Perfil de expressão de RNAm dos genes TNFA, IFNG, ARG1 E CCL2 em células polimorfonucleares nos dias 12 e 18 de gestação em vacas de corte - Teixeira, Bibiana Valerio da Rosa (2022)
Cattle ranching represents a large portion of the Brazilian economy; in addition to its importance in human nutrition, it is related to the supply of raw materials for a diverse range of industries. For the development of a more sustainable and productive livestock, there is a need for research that generates knowledge in its various branches. In view of this need, this work carried out in the area of animal reproduction allows for the improvement of existing techniques and the development of new technologies with an emphasis on the production of beef cattle. In the period of Maternal Recognition of Pregnancy (RMG) in ruminants, the main event is the production of a molecule called interferon-tau (IFNT) by the embryo, secreted by ruminant trophoblast cells before the implantation period, which exerts functions in the most diverse cell types, including Immune System (IS) cells. The immune response plays an important role in the body's defense against infectious agents, with neutrophils, polymorphonuclear leukocytes (PMN) being the primary mediators of the innate immune response and the most abundant cellular component of the IS. The IFNT has essential functions for the maintenance of pregnancy, such as blocking the PGF2a production cascade; it is also an important regulator of maternal immune response, acting directly on the endometrium to stimulate the expression of genes capable of regulating receptivity to embryo implantation. The immune cell response to IFNT can be classically characterized by the expression of ISGs, but also by the expression of pro- and antiinflammatory genes. Neutrophils, or PMNs, respond to IFNT around day 14 of gestation, earlier than other immune cells, and with much stronger gene expression, implying that these cells are more sensitive and that their lifespan life can affect sensitivity to IFNT. This study demonstrated the expression profile of anti- and pro-inflammatory genes during maternal recognition of pregnancy, in order to understand their behavior. Based on the effects of pregnancy on the innate immune response, the hypothesis of the present study is that early pregnancy modulates the PMN response. This study aims to describe the expression profile of pro-inflammatory and anti-inflammatory genes in PMNs from pregnant cows. In order to assist broader studies on RMG, knowledge about the modulation of the TNFA, IFNG, ARG1 and CCL2 mRNA expression profile on days 12 and 18 provides information to establish the endocrine pattern of these genes during the early gestation period in PMNs.